KEPEMIMPINAN DAN MOTIVASI PENGARUHNYA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN PONTANG - Alamsyah, Alamsyah; Fatari, Fatari; Istiani, Titania (LP2M Universitas Bina Bangsa, 2024)
The purpose of this research is to determine the influence of leadership and work motivation on employee performance at the Pontang District Office. The method used in this research is a quantitative descriptive method with correlational analysis. The population in this study was 32 employees with a sample size of 32 employees taken from the total population or what is called a saturated sample. The results of testing hypothesis 1, leadership has no effect on employee performance, obtained a T value (T count 0.882 < T table 2.045), hypothesis 2 motivation has a significant effect on employee performance, obtained a t value (t count 3.332 > t table 2.045). Simultaneously the work environment and motivation for employee performance are shown by the Fcount value of 49.989 > Ftable 3.32. Partially, leadership has no effect on employee performance, but simultaneously leadership and motivation have an effect on employee performance with a contribution of 77.5%.